Plasma-based Radar Cross Section Reduction - Singh, Hema.; Antony, Simy.; Jha, Rakesh Mohan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a comprehensive review of plasma-based stealth, covering the basics, methods, parametric analysis, and challenges towards the realization of the idea. The concealment of aircraft from radar sources, or stealth, is achieved through shaping, radar absorbing coatings, engineered materials, or plasma, etc. Plasma-based stealth is a radar cross section (RCS) reduction technique associated with the reflection and absorption of incident electromagnetic (EM) waves by the plasma layer surrounding the structure. A plasma cloud covering the aircraft may give rise to other signatures such as thermal, acoustic, infrared, or visual. Thus it is a matter of concern that the RCS reduction by plasma enhances its detectability due to other signatures. This needs a careful approach towards the plasma generation and its EM wave interaction. The book starts with the basics of EM wave interactions with plasma, briefly discuss the methods used to analyze the propagation characteristics of plasma, and its generation. It presents the parametric analysis of propagation behaviour of plasma, and the challenges in the implementation of plasma-based stealth technology. This review serves as a starting point for the graduate and research students, scientists and engineers working in the area of low-observables and stealth technology.
Introduction -- EM Wave Propagation through Plasma -- Plasma based RCS Reduction -- Challenges in Plasma-based RCS Reduction -- Conclusion -- References.
Keywords: Engineering mathematics; Engineering$1 (BData processing.s; Plasma (Ionized gases).; Telecommunication; Mathematical and Computational Engineering Applications; Plasma Physics; Microwaves, RF Engineering and Optical Communications